A Testimony of the Surgent SARS-CoV-2 in the Immunological Panorama of the Human Host - Minakshi, Rinki; Jan, Arif Tasleem; Rahman, Safikur; Kim, Jihoe (Frontiers in Cellular and Infection Microbiology, 2020)
The resurgence of SARS in the late December of 2019 due to a novel coronavirus, SARS-CoV-2, has shadowed the world with a pandemic. The physiopathology of this virus is very much in semblance with the previously known SARS-CoV and MERS-CoV. However, the unprecedented transmissibility of SARS-CoV-2 has been puzzling the scientific efforts. Though the virus harbors much of the genetic and architectural features of SARS-CoV, a few differences acquired during its evolutionary selective pressure is helping the SARS-CoV-2 to establish prodigious infection. Making entry into host the cell through already established ACE-2 receptor concerted with the action of TMPRSS2, is considered important for the virus. During the infection cycle of SARS-CoV-2, the innate immunity witnesses maximum dysregulations in its molecular network causing fatalities in aged, comorbid cases. The overt immunopathology manifested due to robust cytokine storm shows ARDS in severe cases of SARS-CoV-2. A delayed IFN activation gives appropriate time to the replicating virus to evade the host antiviral response and cause disruption of the adaptive response as well. We have compiled various aspects of SARS-CoV-2 in relation to its unique structural features and ability to modulate innate as well adaptive response in host, aiming at understanding the dynamism of infection.